PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KEPUASAN KARYAWAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (PERUSAHAAN AGENCY) - Sarah Virgianty; Subarjo Joyosumarto; Antyo Pracoyo; Enny Haryanti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study analyzes the influence of transformational leadership, employee satisfaction, compensation and work environment on employee performance in agency companies in Greater Jakarta. Data were collected from 108 respondents in Greater Jakarta with at least one year of work experience and analyzed using Partial Least Square (PLS). The findings show that transformational leadership and work environment significantly and positively affect performance, while employee satisfaction and compensation have a positive but insignificant effect. Simultaneously, all four variables show a positive but insignificant influence. These results highlight the importance of transformational leadership and a supportive work environment, along with improvements in compensation systems and strategies to enhance employee satisfaction.